A formal, scalable approach to semantic interoperability - Davies, J; Welch, J; Milward, D; Harris, S (Elsevier, 2020)
Scientific progress is increasingly dependent upon the acquisition, processing, and analysis of large volumes of data. The validity of results and the safety of applications rely upon an adequate understanding of the real-world semantics of this data: its intended interpretation, and the context in which it is acquired and processed. This presents a challenge: interpretations vary, context is infinite, and either may change over time.